The Implementation of Diverse Actuation System in ACPR1000 Nuclear Power Plants - Zhen-Ying Wang; Zhi-Yun Liu; Ting-Wei Ma; Chen Sun; Liu Liu; Yu Huang; Gang-Miao Guo (Science and Technology of Nuclear Installations)
In order to improve the capability of dealing with software common cause failure (CCF) of digital reactor protection and monitoring system (RPMS), the diverse actuation system (DAS) is introduced for ACPR1000 nuclear power plants. From economic and feasibility point of view, the solution of DAS sharing with RPMS sensors and actuators is suggested; after capturing the function requirement of DAS, the automatic functions and manual functions assigned to it are determined based on transient analysis of design basic accidents concurrent with software CCF of RPMS. The independent verification proves that the reactor can be fallen back to and maintained at safety shutdown state, thanks to these DAS functions. Insight into probabilistic safety assessment proves significant reductions of risks are contributed. The critical technical issues while implementing DAS, such as measures to ensure its diversity from RPMS, precautions for preventing from its spurious actuation, isolation and independency from RPMS, and its testability and maintainability, are deliberately settled to improve its engineering reliability and alleviate the impact on RPMS as far as possible. Field programmable gate array technology that is diversified from RPMS is chosen to build DAS of ACPR1000 nuclear power plant, and the commissioning test verifies that it is capable of performing its designed functions. At last, a set of DAS-specific, paper-based, and event-oriented emergency operating procedure is developed, verified, and validated. Until now, the DAS system has always been successfully operating in all ACPR1000 nuclear power plants for several years.